Chemopreventive and Anticancer Property of Selenoproteins in Obese Breast Cancer - Bevinakoppamath, Supriya; Saleh Ahmed, Adel Mohammed; Ramachandra, Shobha Chikkavaddaraguddi; Vishwanath, Prashant; Prashant, Akila (Frontiers in Pharmacology, 2021)
Obesity is a significant risk factor for various cancers including breast cancer resulting in an increased risk of recurrence as well as morbidity and mortality. Extensive studies on various pathways have been successful in establishing a biological relationship between obesity and breast cancer. The molecular classification of breast cancer includes five groups each having different responses to treatment. Increased levels of inflammatory cytokines seen in obese conditions drive the pro-proliferative pathways, such as the influx of macrophages, angiogenesis, and antiapoptotic pathways. Increased peripheral aromatization of androgens by aromatase increases the circulating estrogen levels which are also responsible for the association of obesity with breast cancer. Also, increased oxidative stress due to chronic low-grade inflammation in obese women plays an important role in carcinogenesis. Despite the availability of safe and effective treatment options for breast cancer, obese women are at increased risk of adverse outcomes including treatment-related toxicities. In the recent decade, selenium compounds have gained substantial interest as chemopreventive and anticancer agents. The chemical derivatives of selenium include inorganic and organic compounds that exhibit pro-oxidant properties and alter cellular redox homeostasis. They target more than one metabolic pathway by thiol modifications, induction of reactive oxygen species, and chromatin modifications to exert their chemopreventive and anticancer activities. The primary functional effectors of selenium that play a significant role in human homeostasis are selenoproteins like glutathione peroxidase, thioredoxin reductase, iodothyronine deiodinases, and selenoprotein P. Selenoproteins play a significant role in adipose tissue physiology by modulating preadipocyte proliferation and adipogenic differentiation. They correlate negatively with body mass index resulting in increased oxidative stress that may lead to carcinogenesis in obese individuals. Methylseleninic acid effectively suppresses aromatase activation thus reducing the estrogen levels and acting as a breast cancer chemopreventive agent. Adipose-derived inflammatory mediators influence the selenium metabolites and affect the proliferation and metastatic properties of cancer cells. Recently selenium nanoparticles have shown potent anticancer activity which may lead to a major breakthrough in the management of cancers caused due to multiple pathways. In this review, we discuss the possible role of selenoproteins as chemopreventive and an anticancer agent in obese breast cancer.